Study guides

☆☆

Q: What is 2a plus 3b plus 4a?

Write your answer...

Submit

Still have questions?

Related questions

8b -2a

11a+7b-(3b-2a)

2a+(-11b)

2 x (2a + 3b - 6)

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

(2a + b)(a + 3b)

4a

2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.

1a+3b 2a+4b=3a +7b

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

2a + 3b

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

That factors to (2a - 7)(2a + 9)

2a + 9 = 4a - 19 9 + 19 = 4a - 2a 28 = 2a a = 14

2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.

2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4

6+7a+6b

4a+3b can not be algebraically simplified. It can be evaluated if you assign values to a and b.

The expression is: (4a+b)/(2a-5b)

11a+11b

58

2a+6b

2a-6a+9-4a+9

It is 2a-b simplified